2022
DOI: 10.3389/fcvm.2022.840262
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multi-Modal Data and Machine Learning to Improve Cardiovascular Disease Care

Abstract: Today's digital health revolution aims to improve the efficiency of healthcare delivery and make care more personalized and timely. Sources of data for digital health tools include multiple modalities such as electronic medical records (EMR), radiology images, and genetic repositories, to name a few. While historically, these data were utilized in silos, new machine learning (ML) and deep learning (DL) technologies enable the integration of these data sources to produce multi-modal insights. Data fusion, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Recent advances in the field of machine learning have improved the discovery of new biomarkers for disease diagnosis or helped in designing treatment plans [ 14 , 25 , 26 , 27 ]. Dundar et al [ 28 ] utilized a proposed machine-learning surgical planning and found that it significantly contributed to positive outcomes for neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the field of machine learning have improved the discovery of new biomarkers for disease diagnosis or helped in designing treatment plans [ 14 , 25 , 26 , 27 ]. Dundar et al [ 28 ] utilized a proposed machine-learning surgical planning and found that it significantly contributed to positive outcomes for neurosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this research field is to incorporate the unlabeled data from the occupational injury report such as text narratives and injury images with the labeled data to improve the predictive capabilities of the model [ 55 ]. As suggested by [ 56 ], the use of the deep learning method using the Generative Adversarial Network (GAN) can assist in medical diagnosis with full utilization of labeled and unlabeled data.…”
Section: Discussionmentioning
confidence: 99%
“…These notes are extracted from the narrative reports prepared by the Safety and Health Engineer and Occupational Health Doctor. This is the highlight of using multimodal data learning since it necessitates the integration of expertise in domain knowledge and technical aspects ( 56 , 69 ), enhancing the successful applications of the predictive model of occupational injury outcomes.…”
Section: Discussionmentioning
confidence: 99%